Learning from the Past, Planning for the Future... - Blanche Cameron (Papers from the Institute of Archaeology, 2013)
Ever since the National Planning Policy Framework hove into view, it has been polarising opinions, either for or against this most radical shake up of UK planning policy since just after the Second World War. Suddenly, what was a highly (some say over) complex system of thousands of pages of detailed planning guidance has been simplified to a 58 page document, which has been through a year of consultation before coming into law. It is interesting to consider how the NPPF is now being viewed and applied in different contexts. Flatman and Perring’s paper explores the potential (positive and negative) impacts of the NPPF on archaeological practice, in terms of conservation, but also in social and cultural terms – the fear being that, without the proper requirements in place, archaeological evidence may at best be conserved, but without sufficient capacity to research, understand and integrate its meaning for us and our future.
Keywords: National Planning Policy Framework; planning; development